The Influence of Product Quality and Price on Purchasing Decisions of Glad2glow Skincare Products - Krey, Elvira Jaslin; Dananjaya, Irwandaru (Golden Ratio of Data in Summary, 2024)
This research is based on a phenomenon in the modern era where consumers are increasingly aware of the importance of skin care, making skincare products the main choice to support appearance. Glad2Glow, a new skincare brand that entered the Indonesian market in 2023, has attracted a lot of buyers' attention and created fierce competition between brands with product quality and price perception as the main factors in consumers' purchase decisions. This research is quantitative using primary data obtained through the distribution of online questionnaires (Google Form) from May 2024 to August 2024. The population and sample include all consumers who have purchased or used Glad2Glow skincare products. The independent variables are product quality (X1) and price perception (X2), while the dependent variable is the purchase decision (Y). The analysis method involves multiple linear regression analysis, validity and reliability tests, as well as classical assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests, and hypothesis tests. The results of this study show that (1) product quality variables have a partial effect on the purchase decision of Glad2Glow skincare products, (2) price perception variables have a partial effect on the purchase decision of Glad2Glow skincare products, (3) product quality variables and price perception have a simultaneous effect on the purchase decision of Glad2Glow skincare products.